An Enterprise Architecture Plan for Training Center of IIB Darmajaya - M Said Hasibuan; Hendri Purnomo; Melda Agharina (Proceeding International Conference on Information Technology and Business, 2020)
The Training Center of Institute of Informatics and Business (IIB) Darmajaya was one of the technical implementation units that facilitated the needs of IIB Darmajaya and stakeholders to achieve superior quality graduates. This Training Center had prospective alumni who were distributed their training skills needed by stakeholders. This Training Center was not able to provide integrated services, e.g., optimizing the inadequate service. The objective of this study was to design the enterprise architecture (EA) using TOGAF framework to solve the problem. The procedure of this study was carried out through the preliminary phase, architecture vision, business architecture, information systems and technology architecture. The result of this study was designing novel models by using TOGAF EA.Keywords: TOGAF, Enterprise Architecture, Darmajaya